2022
DOI: 10.3389/fpls.2022.835943
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Taxonomic Significance of Seed Micromorphology in Impatiens (Balsaminaceae)

Abstract: Impatiens is one of the most species-rich genera of angiosperms, with more than 1,000 species distributed in Eurasia and Africa. Previous studies have shown that seeds of Impatiens display enormous morphological diversity, and seed micromorphology may contribute to the classification of those species. However, the micromorphological seed coat characteristics of Impatiens seeds have not been systematically studied. In this study, we examined 117 Impatiens seeds from two subgenera and seven sections, and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The topologies built from the two datasets were mutually congruent and the inferences were consistent with the conclusions of other studies [ 40 , 49 52 , 54 ]. The systematic position of the section has previously been debated, apparently due to the limited number of molecular markers [ 40 , 54 ]. However, we were able to confirm the sister relationship between sect.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The topologies built from the two datasets were mutually congruent and the inferences were consistent with the conclusions of other studies [ 40 , 49 52 , 54 ]. The systematic position of the section has previously been debated, apparently due to the limited number of molecular markers [ 40 , 54 ]. However, we were able to confirm the sister relationship between sect.…”
Section: Discussionsupporting
confidence: 87%
“…The greater breadth of our taxon sampling revealed a new clade, Clade III, with strong support and unambiguous internal relationships. In previous studies, perhaps due to the low resolution of molecular markers and limited sampling based on only two taxa from this clade, namely, I. apsotis and I. tortisepala , the phylogenetic positions of these two species were incongruent such that they were not considered to be part of a separate clade [ 40 , 50 , 51 , 54 ]. Extensive sampling in our study has also allowed the major clades to be re-circumscribed, as the ambiguous phylogenetic positions of several species were resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf, flower, and pollen micromorphology has been informative for resolving taxonomic problems in angiosperms across various taxonomic levels 1 7 . In particular, leaf epidermal stomata, orbicules, and pollen exine ornamentation characters have been shown to possess systematic values when examined using both light microscopy (LM) and scanning electron microscopy (SEM) and may further be utilized to test phylogenetic hypotheses 8 13 . However, despite an increasing number of the leaf, flower, pollen, and seed micromorphological studies in Iridaceae 14 21 , leaf margins, stomatal occurrence, and orbicular traits have not been considerably challenged for the taxonomic delineation of two closely related species, Iris ruthenica and I. uniflora .…”
Section: Introductionmentioning
confidence: 99%
“…In general, we analyzed the character evolution of pollen and macroscopic traits as well as seedcoat ornamentation (Utami & Shimizu, 2005; Yu, 2012; Song et al, 2022) in Impatiens and found an obvious mosaic evolution in this genus. In other words, the evolutionary rate of different traits in this genus was inconsistent.…”
Section: Discussionmentioning
confidence: 99%